Fever, Cough and Cold What else do you have? Impact of the Sars-Cov-2 Pandemic in the consultation for respiratory diseases in the pediatric emergency: Fiebre, Tos y Resfrío ¿Qué más tiene? Impacto de la Pandemia por Sars-Cov-2 en la consulta por enfermedades respiratorias en la emergencia pediátrica - Pavlicich, Viviana (2020)
When fall arrives, pediatric emergency services (SEP) professionals know before the trees decide to change their leaves. The increase in the number of patients is as important as the repetition of the reasons for consultation and the explanations about the futility of ¨treatments for viruses¨. In addition to colds with and without fever that lead EPS to collapse, there are severe symptoms of bronchiolitis, laryngitis, asthma attacks and pneumonia that demand specialized care.